SOIL WATER CHARACTERISTICS OF TWO AGRO-ECOLOGICAL ZONES OF KATSINA STATE, NIGERIA: A COMPARISON STUDY BETWEEN THE SOILWAT MODEL AND LABORATORY TEST - Ojo, B. S.; Maina, M. M. (FUDMA JOURNAL OF SCIENCES, 2023)
Soil water characteristics (SWC) is essential for studying water availability for plants, plant water stress, infiltration, water conductivity, drainage and irrigation scheduling. However, field determination of available soil water is often laborious and time consuming. In lieu of this, SOILWAT model can be used. The experiment covers two agro-ecological zones of Katsina State to compare results of SOILWAT model prediction of soil water characteristics and measured results of different soil depth of Katsina State. 84 soil samples were collected at depths 0 to 30 and 30 to 60 cm for top and subsoil respectively at 7 locations in the zones and reference points also recorded. The measured and predicted values of the SWC were compared using, mean bias of error, range and kriged form of interpolation map using GIS Software. The results of the predicted soil textural classes obtained from the SOILWAT model were similar to the measured textural classes for Sudan Savanna (SS) and Northern Guinea Savanna (NGS), however, the SS soils have more sand components than NGS
Keywords: Water conductivity, Model prediction, Soil depth, GIS Software